(untitled) (CIPEEX, 2025)
The software presents the development of an automated notification system for the Fire Department, aimed at optimizing the management of essential operational processes such as warehouse inventory control, inspections, certificate renewals, and project analysis. The methodology is based on the integration of automatic alerts that monitor certificate expiration dates, material inventory levels, inspection needs, and the project review workflow, ensuring that the department can act proactively. The notification system is powered by reports from PagHiper and a barcode-based inventory control system, which triggers warnings when items reach critical levels. The results show a significant reduction in deadline compliance failures and improved internal organization, particularly in certificate management and material control. The proposed system aims to provide a robust solution to the recurring challenges faced by the Fire Department in managing its internal processes, especially in critical areas like inventory control and certificate renewal. The approach automates the detection of minimum stock conditions, activating notifications so that new orders are placed before material levels affect operations. Similarly, the system ensures that inspections are scheduled in advance, guaranteeing that equipment and facilities always comply with legally required safety standards. The certificate renewal notifications, generated based on PagHiper reports, offer an additional layer of control, preventing fines or penalties due to expired deadlines.Another crucial aspect is the integration of an automated workflow for project analysis, ensuring that responsible parties are notified when new reviews are needed, reducing delays in the approval process. The barcode-based control system makes inventory management more precise and traceable, providing a clear view of available materials and avoiding unnecessary purchases. This solution integrates all these processes into a centralized platform, providing real-time visibility and control for managers. With this automation, the department can ensure greater efficiency, reduce reliance on manual interventions, and increase the reliability of operations, promoting both internal and external safety.